Comparative Analysis of The Competitiveness of Turkey's Iron-Steel Industry - KESGİNGÖZ, Hayrettin; DİLEK, Serkan; YELDAN, Muharrem (Journal of the Human and Social Sciences Researchers, 2019)
The values of the Grubel-Lloyd, Vollrath and CEP indices are important indices used to show the countries' competitiveness levels. Turkey wants to prove and maintain its presence in the iron and steel sector, which has been the locomotive sector of industrialization for years. Turkey's iron and steel industry competitiveness, to a comparative analysis with other countries Grubel-Lloyd, volrath and Kip indices were calculated for the years 2001-2017. As a result of analysis, Turkey; it operates in-industry trade against the USA, Germany, China, Britain and Russia. In Addition, it has a comparative advantage in the field of iron and steel and its competitiveness is quite high. The country where we have the highest competitive power and export share from these 5 countries is USA, considering the intra-industry trade values. The USA is followed by China, Britain, Germany and Russia respectively. In industrial trade, which is the feature of Industrialised Country, Turkey sells significant amounts of iron-steel out and also buys it from outside. Considering these analyses; In the iron and steel sector, which is a capital intensive sector, iron-steel sector investments should be encouraged in order to maintain the increase continue in competitiveness observed against the USA, Germany, China, Britain and Russia and to increase its competitiveness. For this, financial arrangements such as the necessary infrastructure investments and tax incentives appear to be a viable policy.
Keywords: 9. Industry and infrastructure; 8. Economic growth; 1. No poverty; 12. Responsible consumption